(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Copolymer p-hydroxybenzoic acid urea formaldehyde(PUF) was prepared from the reaction of p- hydroxybenzoic acid(P) + urea(U) + formaldehyde(F) using HCl as a catalyst. Formation of Pb(II),Zn(II) and Cd(II) polymers were obtained from the reaction of the copolymer (PUF) with some ions. The polymeric structures were elucidated by Fourier transform infrared spectroscopy (FTIR) and Atomic Absorption spectroscopy (AA), thermogravimetric analysis (TGA) and derivative of the thermogravimetric analysis (DTG) has been carried out to ascertain relative thermal stability of copolymer and its polymeric complexes and the pat of H2O in the structure. Form the obtained data an octahedral geometry around Pb(II),Zn(II) and Cd(II) )ions have been suggested